Nomenclatural transfer of Manfreda arceliensis to Agave (Asparagaceae) - Idrees, Muhammad; Zhang, Zhiyong (Phytotaxa, 2023)
For the recently published Manfreda arceliensis from Mexico, a binomial in Agave is proposed: Agave arceliensis (Art.Castro, J.G. Zavala & Cruz Durán) Idrees & Z.Yong Zhang, comb. nov. Additionally, the name Manfreda justosierrana (≡ Agave justosierrana) is lectotypified here.